Educação em Contextos Humanitários - Maria Eyng, Ana; Casqueira Cardoso, João; Alberto da Costa Gomes, Candido; Teresa Prieto Quezada, Maria; Dudeque Pianovski Vieira, Alboni (Revista Diálogo Educacional, 2024)
.